(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Plastic trash production and disposal pose a serious threat to the environment, causing pollution and global warming. The characteristics and strength of plastic trash used in bituminous roads and pavements are improved. Also, it will be beneficial forIndia as a way to handle plastic waste disposal and numerous road/pavement flaws including ruts, potholes, corrugation, etc. Polythene, polystyrene, and polypropylene are the types of plastic trash that are used. The waste plastic is crushed, covered with gravel, and combined with hot bitumen to create a mixture thatis used to build roads and pavement. The pavement willbe strengthened and become more durable as a result. Its ground-breaking technology will also work in India’s hot, humid climate. Both environmentally sustainable and cost-effective.